Decentralizacja finansów publicznych w Polsce i wybranych państwach Europy - Bal-Domańska, Beata (Decentralization of Public Finance in Poland and Selected European Countries, 2006)
Public finance, its structure, the level of balance become one of the major elements, which decide about taking advantage of developmental opportunities in economy and the lifestyle level in a society, consequently becoming the decisive factor related to the capacity of financing basic state functions and co-financing economy modernisation. The subject of public finance is directly connected with decentralisation problems and becomes a frequent topic for discussions in professional literature all over the world. The most popular problem raised by local authorities units, regardless of the state itself, is the problem of their financial independence. The article presents the most important issues related to public finance decentralization in Poland, Germany and France.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 539-550